2013
DOI: 10.1093/ejcts/ezt195
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of mediastinal node cancer after lobe-specific systematic nodal dissection for non-small-cell lung cancer

Abstract: The recurrence of mediastinal node cancer in patients undergoing L-SND was significantly greater than that in those undergoing SND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 22 publications
1
50
0
1
Order By: Relevance
“…On the other hand, the reported benefit that SLND can shorten the entire medical period along with its validity, reliability and applicability are still not very clear. Moreover, SLND was reported increasing the possibility of recurrence (35). In order to provide unambiguous answer, multi-institutional randomized clinical trials are expected to carry out in the future.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the reported benefit that SLND can shorten the entire medical period along with its validity, reliability and applicability are still not very clear. Moreover, SLND was reported increasing the possibility of recurrence (35). In order to provide unambiguous answer, multi-institutional randomized clinical trials are expected to carry out in the future.…”
Section: Discussionmentioning
confidence: 99%
“…However, they did not investigate tumor recurrence. We also compared survival, morbidity, and the recurrence pattern between the clinico-surgical N0 NSCLC patients who underwent lobectomy with SND and LSD (17). When we excluded part-solid tumors with a small area of consolidation resulting in a consolidation/tumor ratio of <0.5 from the analysis, there were no significant differences in postoperative complication rates, 5-year overall and disease-free survival rates, or overall recurrence rates between SND and LSD groups.…”
Section: Editorialmentioning
confidence: 99%
“…Asamura (14) reported that tumors of the right lower lobe with superior mediastinal metastasis were associated with a poorer 5-year survival rate of 4.1%. Based on the results of the lobe-specific patterns of nodal metastases, lobe-specific nodal dissection (LSD) has been developed (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…Saeteng et al (13) reviewed 197 patients [including: RUL n=63 (31.98%), RLL n=30 (15.23%), LUL n=55 (27.92%), LLL n=16] and did not observe tumor location to be a precise predictor of the LN-metastasis pattern, rendering complete-MLND the only way to accurately determine LN status. Maniwa et al (14) confirmed that both superior and inferior mediastina were most frequently involved in case of multi-station pN2, a situation that was rarely diagnosed during work-up and commonly discovered by surgery. The recurrence of mediastinal LN cancer was significantly greater in patients undergoing "lobe-specific" LNdissection (LSLND) than in those undergoing complete-MLND (14).…”
mentioning
confidence: 96%
“…Maniwa et al (14) confirmed that both superior and inferior mediastina were most frequently involved in case of multi-station pN2, a situation that was rarely diagnosed during work-up and commonly discovered by surgery. The recurrence of mediastinal LN cancer was significantly greater in patients undergoing "lobe-specific" LNdissection (LSLND) than in those undergoing complete-MLND (14). They suggested that systematic complete-MLND was not only the option to accurately determine LN status but also a way to decrease the rate of mediastinal recurrence.…”
mentioning
confidence: 96%